Pengembangan Buku Ajar Perkoperasian Indonesia Dalam Perkuliahan Mahasiswa Prodi Pendidikan Ekonomi - Putri Vina Sefaverdiana; Melisa Wahyu Fandyansari (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2020)
Indonesian Cooperative textbooks are development research aimed at developing quality textbooks and can effectively improve understanding of existing cooperatives in Indonesia. Textbooks as a support in Cooperative lectures, in order to improve student learning in class so that students have understanding and skills in cooperating. The purpose of this textbook is to make it easier for students to learn and understand as a provision for students to develop cooperatives in their respective areas of residence. The method in this research is a research and development research using a model from Dick and Carrey. The test results obtained from the first material expert were 84.5%, the second material expert obtained 76.4%. 3%. After the expert test was carried out a small-scale test where the result was 82.6% and the large-scale test obtained a result of 86.3%. From the results of the percentage, it states that the textbook is in the good category and is feasible to apply